Opioid substitution treatment with sublingual buprenorphine in Manipur and Nagaland in Northeast India: what has been established needs to be continued and expanded - Sharma Charan; Langkham B; Natale Richard D; Kumar M Suresh; Kabi Rachel; Mortimore Gordon (BMC, 2009)
Abstract Manipur and Nagaland in northeast India report an antenatal HIV prevalence of > 1% and the current HIV prevalence among injecting drug users is 24% and 4.5% respectively. Through support from DFID's Challenge Fund, Emmanuel Hospital Association (EHA) established thirteen drop-in-centres across the two states to deliver opioid substitution treatment with sublingual buprenorphine for 1200 injecting drug users. Within a short span of time the treatment has been found to be attractive to the clients and currently 1248 injecting opioid users are receiving opioid substitution treatment. The project is acceptable to the drug users, the families, the communities, religious as well as the militant groups. The treatment centres operate all days of the week, have trained staff members, utilize standardized protocols and ensure a strict supervised delivery system to prevent illicit diversion of buprenorphine. The drug users receiving the substitution treatment are referred to HIV voluntary counselling and testing. As this treatment has the potential to change HIV related risk behaviours, what has been established in the two states needs to be continued and expanded with the support from the Government of India.